ANALISIS PENGARUH KUALITAS PELAYANAN KEPUASAN HARGA TERHADAP KEPUTUSAN PEMBELIAN SWALAYAN NABILA YOGYAKARTA - Dewanto, Mega Ria; Asakdiyah, Salamatun (Universitas Ahmad Dahlan, 2015)
Retail business in Indonesia has developed quite rapidly in the last few years with various forms and types. Competition in the retail or retail business which is currently increasingly fierce forces retail or retail business entrepreneurs to compete with each other to try to attract the attention of consumers. This study aims to determine and analyze the variables of service quality, satisfaction and price partially or jointly with purchasing decisions at the Nabila supermarket in Yogyakarta. In this study the sample used was a portion of Nabila Yogyakarta self-service consumers using Purposive Sampling techniques totaling 100 people. The analysis technique used is multiple linear regression analysis. The results of this study are that Service Quality has a positive and significant influence on the purchasing decisions of Nabila Supermarket customers in Yogyakarta with a regression coefficient of 0.409 (positive) and a tcount of 3.351 and a probability of error (p) = 0.001. Satisfaction variable has a positive and significant influence on the purchasing decisions of Nabila Supermarket customers in Yogyakarta with a regression coefficient of 0.249 (positive) and a tcount of 2.466 and p = 0.015. Price variable has a positive and significant influence on customer purchasing decisions in Nabila Yogyakarta with a regression coefficient of 0.336 (positive) and the significance test for the coefficient obtained is 3.751 and p = 0.000. Variable Service Quality, Satisfaction and Price simultaneously influence the customer purchasing decisions on users of Yogyakarta Nabila Supermarket with F statistics obtained by Fcount of 17.961 and the probability of error (p) = 0,000.